Supernova light-curve fitters and Dark Energy - Bengochea, Gabriel Roman (2011)
We show that when a procedure is made to remove the tension between a supernova Ia (SN Ia) data set and observations from BAO and CMB, there might be the case where the same SN Ia set built with two different light-curve fitters behaves as two separate and distinct supernova sets, and the tension found by some authors between supernova sets actually could be due to tension or inconsistency between fitters. We also show that the information of the fitter used in an SN Ia data set could be relevant to determine whether phantom type models are favored or not when such a set is combined with the BAO/CMB joint parameter